An Evaluation of the Evil Characters in Shakespeare’s Four Main Tragedies in terms of Machiavellian Principles - Ayyıldız, Nilay Erdem (My University, 2019)
Deriving from Italian political philosopher Niccolò Machiavelli, the term ‘Machiavellian’ refers to a ruler type,whose features are described in his work The Prince (1513). In the work, Machiavelli mentions the principles aruler should follow to obtain and hold power by disregarding all main rules of morality such as faithfulness,honesty. In this context, Machiavelli provided a new type of villain for the Elizabethan and Jacobean revengetragedy. The study claims that Shakespearean tragedies including Othello, King Lear, Hamlet and Macbethregarded as his “four principle tragedies” (Hazlitt, 2009, p. 21) also contain Machiavellian characters. It aims atexamining villains in the plays in terms of Machiavellian principles and discuss to what extent they areMachiavellian throughout the plays. Machiavelli’s The Prince is taken as a guide to analyse the Machiavellianfeatures of the characters in question. It reveals that Iago and Edmund are Machiavellian because of theircapabilities of responding to unexpected events and manipulating conditions ignoring any moral values due totheir perspicacity throughout the plays. However, compared to Edmund, Iago falls short of Machiavellianismbecause of his groundless malignancy. On the other hand, it is revealed that the other examined characters,Regan, Goneril, Claudius, and the Macbeth couple fail in the way of Machiavellianism at last even though theyare also evil in nature. The study asserts that in contrast to Machiavellian’s remarks, Shakespeare was of theopinion that a Machiavellian, whether or not successful, does both himself/herself and the society harm.
Keywords: Edebiyat; Edebi Teori ve Eleştiri